2022
DOI: 10.1007/s43465-021-00585-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Therapeutic Outcomes of Transabdominal Pararectus Approach and Modified Stoppa Approach in Treating Pelvic and Acetabular Fractures

Abstract: Objective Pelvic and acetabular fractures are common orthopedic diseases, and this research was to investigate the therapeutic effects of pararectus and Stoppa approaches in treating complex pelvic acetabular fractures. Methods The clinical information of patients with pelvic and acetabular fractures treated surgically in Lu'an Hospital of Chinese medicine, China from January 2016 to April 2020 was analyzed. There were 30 cases each in the transabdominal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Many studies have demonstrated that although the rate of anatomical repositioning in elderly patients with acetabular fractures is lower than that in younger patients, long-term functional outcomes remain satisfactory and only a minority of patients require a repeat total hip replacement. Therefore, for elderly patients with acetabular fractures with obvious displacement, except for some special types of fractures that need one-stage total hip arthroplasty, open reduction and internal fixation should be the first choice [ 28 ]. In order to reduce the incidence of postoperative hip pain, traumatic osteoarthritis, and failure of internal fixation, acetabular fracture surgery should achieve hip white anatomical reconstruction and maintain concentric reduction of the hip joint [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that although the rate of anatomical repositioning in elderly patients with acetabular fractures is lower than that in younger patients, long-term functional outcomes remain satisfactory and only a minority of patients require a repeat total hip replacement. Therefore, for elderly patients with acetabular fractures with obvious displacement, except for some special types of fractures that need one-stage total hip arthroplasty, open reduction and internal fixation should be the first choice [ 28 ]. In order to reduce the incidence of postoperative hip pain, traumatic osteoarthritis, and failure of internal fixation, acetabular fracture surgery should achieve hip white anatomical reconstruction and maintain concentric reduction of the hip joint [ 29 ].…”
Section: Discussionmentioning
confidence: 99%